Diversity and Potential of Medicinal Plants at PT Indocement Tunggal Prakarsa Cirebon Indonesia - Yayan Hendrayana; Nina Herlina; Iing Nasihin; Ilham Adhya; Rufidi Chandra; Martinus Ari Kristanto; Suswanto (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
Medicinal plants have high value and have long been used in traditional medicine. Indonesia is rich in plants with medicinal potential, but their utilization faces challenges such as environmental degradation and lack of research. PT Indocement Tunggal Prakarsa Palimanan Cirebon is committed to maintaining biodiversity amidst the impacts of its industry. The surrounding area remains a habitat for medicinal plants and ecosystems that support life. This study aims to determine the diversity and potential of medicinal plants in several ecosystems or land cover. Data collection used the grid path method by making observation plots at each location for undergrowth, seedlings, stakes, poles and trees, then analyzed for diversity and potential. The results of the study inform that the diversity of undergrowth dominates each ecosystem and the location of the Blindis Mountain Conservation Area has higher diversity compared to other areas. There are 29 types of undergrowth that have medicinal potential and 31 types of tree habitus at each location that have medicinal potential. These results are important information for companies to manage their areas, especially for plants that have medicinal properties.